Genealogy Of Al-Qurtubi's Interpretation In Countering Radicalism Through Moderate Religious Verses: A Case Study Of Tribunnews.Com's Youtube Channel - Basid, Abdul; Faizin, Nur; Nasih, Ahmad Munjin; Hanafi, Yusuf; Ramadhan, Mohammad Rizal; Bkheet Ahmed, Bakri Mohammed (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study aims to examine the genealogy of the verse of religious moderation in Surat Al-Baqarah verse 143 and the efforts contained in the verse to counteract radicalism in this case sample on the tribunnews.com youtube channel. This study used the method of analysis of maudhu'i tafsir on al-Qurtubi's Ahkam al-Quran tafsir, which is one of the famous Sunni-classical tafsir works. Through the analysis of al-Qurtubi's tafsir, it was found that verse 143 of Surat al-Baqarah shows the importance of moderation in religion, which considers the balance between the interests of the individual and the interests of society. Moderation in religion is also associated with the concept of ummatan wasatan which emphasizes justice and balance in life, and sees the response of tafsir al-Qurtubi to see the phenomenon of radicasim that emerged in Indonesia. In addition, this study shows that verse 143 of Surat Al-Baqarah also provides concrete efforts in countering radicalism, namely by showing the importance of respecting differences and avoiding actions that cause divisions in society. The benefit of this research is to provide a deeper understanding of the verse of religious moderation in Surat al-Baqarah verse 143, as well as contribute to countering radicalism. This research can also be used as a reference for future research on the same theme. Overall, this study shows that verse 143 of Surat al-Baqarah has a broad meaning and can provide useful direction in efforts to counteract radicalism and promote religious moderation.